### (0) Obligation:

Runtime Complexity TRS:
The TRS R consists of the following rules:

from(X) → cons(X, n__from(n__s(X)))
length(n__nil) → 0
length(n__cons(X, Y)) → s(length1(activate(Y)))
length1(X) → length(activate(X))
from(X) → n__from(X)
s(X) → n__s(X)
niln__nil
cons(X1, X2) → n__cons(X1, X2)
activate(n__from(X)) → from(activate(X))
activate(n__s(X)) → s(activate(X))
activate(n__nil) → nil
activate(n__cons(X1, X2)) → cons(activate(X1), X2)
activate(X) → X

Rewrite Strategy: FULL

### (1) DecreasingLoopProof (EQUIVALENT transformation)

The following loop(s) give(s) rise to the lower bound Ω(2n):
The rewrite sequence
activate(n__from(X)) →+ cons(activate(X), n__from(n__s(activate(X))))
gives rise to a decreasing loop by considering the right hand sides subterm at position [0].
The pumping substitution is [X / n__from(X)].
The result substitution is [ ].

The rewrite sequence
activate(n__from(X)) →+ cons(activate(X), n__from(n__s(activate(X))))
gives rise to a decreasing loop by considering the right hand sides subterm at position [1,0,0].
The pumping substitution is [X / n__from(X)].
The result substitution is [ ].

### (3) RenamingProof (EQUIVALENT transformation)

Renamed function symbols to avoid clashes with predefined symbol.

### (4) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

from(X) → cons(X, n__from(n__s(X)))
length(n__nil) → 0'
length(n__cons(X, Y)) → s(length1(activate(Y)))
length1(X) → length(activate(X))
from(X) → n__from(X)
s(X) → n__s(X)
niln__nil
cons(X1, X2) → n__cons(X1, X2)
activate(n__from(X)) → from(activate(X))
activate(n__s(X)) → s(activate(X))
activate(n__nil) → nil
activate(n__cons(X1, X2)) → cons(activate(X1), X2)
activate(X) → X

S is empty.
Rewrite Strategy: FULL

Infered types.

### (6) Obligation:

TRS:
Rules:
from(X) → cons(X, n__from(n__s(X)))
length(n__nil) → 0'
length(n__cons(X, Y)) → s(length1(activate(Y)))
length1(X) → length(activate(X))
from(X) → n__from(X)
s(X) → n__s(X)
niln__nil
cons(X1, X2) → n__cons(X1, X2)
activate(n__from(X)) → from(activate(X))
activate(n__s(X)) → s(activate(X))
activate(n__nil) → nil
activate(n__cons(X1, X2)) → cons(activate(X1), X2)
activate(X) → X

Types:
from :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
cons :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__from :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__s :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
length :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__nil :: n__s:n__from:n__nil:0':n__cons
0' :: n__s:n__from:n__nil:0':n__cons
n__cons :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
s :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
length1 :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
activate :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
nil :: n__s:n__from:n__nil:0':n__cons
hole_n__s:n__from:n__nil:0':n__cons1_0 :: n__s:n__from:n__nil:0':n__cons
gen_n__s:n__from:n__nil:0':n__cons2_0 :: Nat → n__s:n__from:n__nil:0':n__cons

### (7) OrderProof (LOWER BOUND(ID) transformation)

Heuristically decided to analyse the following defined symbols:
length, length1, activate

They will be analysed ascendingly in the following order:
length = length1
activate < length
activate < length1

### (8) Obligation:

TRS:
Rules:
from(X) → cons(X, n__from(n__s(X)))
length(n__nil) → 0'
length(n__cons(X, Y)) → s(length1(activate(Y)))
length1(X) → length(activate(X))
from(X) → n__from(X)
s(X) → n__s(X)
niln__nil
cons(X1, X2) → n__cons(X1, X2)
activate(n__from(X)) → from(activate(X))
activate(n__s(X)) → s(activate(X))
activate(n__nil) → nil
activate(n__cons(X1, X2)) → cons(activate(X1), X2)
activate(X) → X

Types:
from :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
cons :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__from :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__s :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
length :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__nil :: n__s:n__from:n__nil:0':n__cons
0' :: n__s:n__from:n__nil:0':n__cons
n__cons :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
s :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
length1 :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
activate :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
nil :: n__s:n__from:n__nil:0':n__cons
hole_n__s:n__from:n__nil:0':n__cons1_0 :: n__s:n__from:n__nil:0':n__cons
gen_n__s:n__from:n__nil:0':n__cons2_0 :: Nat → n__s:n__from:n__nil:0':n__cons

Generator Equations:
gen_n__s:n__from:n__nil:0':n__cons2_0(0) ⇔ n__nil
gen_n__s:n__from:n__nil:0':n__cons2_0(+(x, 1)) ⇔ n__from(gen_n__s:n__from:n__nil:0':n__cons2_0(x))

The following defined symbols remain to be analysed:
activate, length, length1

They will be analysed ascendingly in the following order:
length = length1
activate < length
activate < length1

### (9) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
activate(gen_n__s:n__from:n__nil:0':n__cons2_0(+(1, n4_0))) → *3_0, rt ∈ Ω(n40)

Induction Base:
activate(gen_n__s:n__from:n__nil:0':n__cons2_0(+(1, 0)))

Induction Step:
activate(gen_n__s:n__from:n__nil:0':n__cons2_0(+(1, +(n4_0, 1)))) →RΩ(1)
from(activate(gen_n__s:n__from:n__nil:0':n__cons2_0(+(1, n4_0)))) →IH
from(*3_0)

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (11) Obligation:

TRS:
Rules:
from(X) → cons(X, n__from(n__s(X)))
length(n__nil) → 0'
length(n__cons(X, Y)) → s(length1(activate(Y)))
length1(X) → length(activate(X))
from(X) → n__from(X)
s(X) → n__s(X)
niln__nil
cons(X1, X2) → n__cons(X1, X2)
activate(n__from(X)) → from(activate(X))
activate(n__s(X)) → s(activate(X))
activate(n__nil) → nil
activate(n__cons(X1, X2)) → cons(activate(X1), X2)
activate(X) → X

Types:
from :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
cons :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__from :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__s :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
length :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__nil :: n__s:n__from:n__nil:0':n__cons
0' :: n__s:n__from:n__nil:0':n__cons
n__cons :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
s :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
length1 :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
activate :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
nil :: n__s:n__from:n__nil:0':n__cons
hole_n__s:n__from:n__nil:0':n__cons1_0 :: n__s:n__from:n__nil:0':n__cons
gen_n__s:n__from:n__nil:0':n__cons2_0 :: Nat → n__s:n__from:n__nil:0':n__cons

Lemmas:
activate(gen_n__s:n__from:n__nil:0':n__cons2_0(+(1, n4_0))) → *3_0, rt ∈ Ω(n40)

Generator Equations:
gen_n__s:n__from:n__nil:0':n__cons2_0(0) ⇔ n__nil
gen_n__s:n__from:n__nil:0':n__cons2_0(+(x, 1)) ⇔ n__from(gen_n__s:n__from:n__nil:0':n__cons2_0(x))

The following defined symbols remain to be analysed:
length1, length

They will be analysed ascendingly in the following order:
length = length1

### (12) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol length1.

### (13) Obligation:

TRS:
Rules:
from(X) → cons(X, n__from(n__s(X)))
length(n__nil) → 0'
length(n__cons(X, Y)) → s(length1(activate(Y)))
length1(X) → length(activate(X))
from(X) → n__from(X)
s(X) → n__s(X)
niln__nil
cons(X1, X2) → n__cons(X1, X2)
activate(n__from(X)) → from(activate(X))
activate(n__s(X)) → s(activate(X))
activate(n__nil) → nil
activate(n__cons(X1, X2)) → cons(activate(X1), X2)
activate(X) → X

Types:
from :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
cons :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__from :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__s :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
length :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__nil :: n__s:n__from:n__nil:0':n__cons
0' :: n__s:n__from:n__nil:0':n__cons
n__cons :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
s :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
length1 :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
activate :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
nil :: n__s:n__from:n__nil:0':n__cons
hole_n__s:n__from:n__nil:0':n__cons1_0 :: n__s:n__from:n__nil:0':n__cons
gen_n__s:n__from:n__nil:0':n__cons2_0 :: Nat → n__s:n__from:n__nil:0':n__cons

Lemmas:
activate(gen_n__s:n__from:n__nil:0':n__cons2_0(+(1, n4_0))) → *3_0, rt ∈ Ω(n40)

Generator Equations:
gen_n__s:n__from:n__nil:0':n__cons2_0(0) ⇔ n__nil
gen_n__s:n__from:n__nil:0':n__cons2_0(+(x, 1)) ⇔ n__from(gen_n__s:n__from:n__nil:0':n__cons2_0(x))

The following defined symbols remain to be analysed:
length

They will be analysed ascendingly in the following order:
length = length1

### (14) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol length.

### (15) Obligation:

TRS:
Rules:
from(X) → cons(X, n__from(n__s(X)))
length(n__nil) → 0'
length(n__cons(X, Y)) → s(length1(activate(Y)))
length1(X) → length(activate(X))
from(X) → n__from(X)
s(X) → n__s(X)
niln__nil
cons(X1, X2) → n__cons(X1, X2)
activate(n__from(X)) → from(activate(X))
activate(n__s(X)) → s(activate(X))
activate(n__nil) → nil
activate(n__cons(X1, X2)) → cons(activate(X1), X2)
activate(X) → X

Types:
from :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
cons :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__from :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__s :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
length :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__nil :: n__s:n__from:n__nil:0':n__cons
0' :: n__s:n__from:n__nil:0':n__cons
n__cons :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
s :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
length1 :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
activate :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
nil :: n__s:n__from:n__nil:0':n__cons
hole_n__s:n__from:n__nil:0':n__cons1_0 :: n__s:n__from:n__nil:0':n__cons
gen_n__s:n__from:n__nil:0':n__cons2_0 :: Nat → n__s:n__from:n__nil:0':n__cons

Lemmas:
activate(gen_n__s:n__from:n__nil:0':n__cons2_0(+(1, n4_0))) → *3_0, rt ∈ Ω(n40)

Generator Equations:
gen_n__s:n__from:n__nil:0':n__cons2_0(0) ⇔ n__nil
gen_n__s:n__from:n__nil:0':n__cons2_0(+(x, 1)) ⇔ n__from(gen_n__s:n__from:n__nil:0':n__cons2_0(x))

No more defined symbols left to analyse.

### (16) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
activate(gen_n__s:n__from:n__nil:0':n__cons2_0(+(1, n4_0))) → *3_0, rt ∈ Ω(n40)

### (18) Obligation:

TRS:
Rules:
from(X) → cons(X, n__from(n__s(X)))
length(n__nil) → 0'
length(n__cons(X, Y)) → s(length1(activate(Y)))
length1(X) → length(activate(X))
from(X) → n__from(X)
s(X) → n__s(X)
niln__nil
cons(X1, X2) → n__cons(X1, X2)
activate(n__from(X)) → from(activate(X))
activate(n__s(X)) → s(activate(X))
activate(n__nil) → nil
activate(n__cons(X1, X2)) → cons(activate(X1), X2)
activate(X) → X

Types:
from :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
cons :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__from :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__s :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
length :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
n__nil :: n__s:n__from:n__nil:0':n__cons
0' :: n__s:n__from:n__nil:0':n__cons
n__cons :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
s :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
length1 :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
activate :: n__s:n__from:n__nil:0':n__cons → n__s:n__from:n__nil:0':n__cons
nil :: n__s:n__from:n__nil:0':n__cons
hole_n__s:n__from:n__nil:0':n__cons1_0 :: n__s:n__from:n__nil:0':n__cons
gen_n__s:n__from:n__nil:0':n__cons2_0 :: Nat → n__s:n__from:n__nil:0':n__cons

Lemmas:
activate(gen_n__s:n__from:n__nil:0':n__cons2_0(+(1, n4_0))) → *3_0, rt ∈ Ω(n40)

Generator Equations:
gen_n__s:n__from:n__nil:0':n__cons2_0(0) ⇔ n__nil
gen_n__s:n__from:n__nil:0':n__cons2_0(+(x, 1)) ⇔ n__from(gen_n__s:n__from:n__nil:0':n__cons2_0(x))

No more defined symbols left to analyse.

### (19) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
activate(gen_n__s:n__from:n__nil:0':n__cons2_0(+(1, n4_0))) → *3_0, rt ∈ Ω(n40)